1998
DOI: 10.1093/nar/26.18.4116
|View full text |Cite
|
Sign up to set email alerts
|

Sequence specificity of the hammerhead ribozyme revisited; the NHH rule

Abstract: The sequence specificity of hammerhead ribozyme cleavage has been re-evaluated with respect to the NUH rule. Contrary to previous reports it was found that substrates with GAC triplets were also cleaved. This was established in three different sequence contexts. The rate of cleavage under single turnover conditions was between 3 and 7% that of cleavage 3' of GUC. Specificity of cleavage of substrates containing a central A in the cleavable triplet can be described as NAH, where N can be any nucleotide and H an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 17 publications
0
37
1
1
Order By: Relevance
“…Despite the latest review of the HHRz, where the cleavage site sequence rule is still regarded as "NUX↓", 25 the study by Eckstein's group suggested that the rule could be revised to "NHH↓". 38 However, the study expected that the rate of GAC cleavage under single turnover conditions would be about 3%-7% compared to GUC, while our work reveals that the catalytic activity of GAC is almost equal to GUC, which is fairly distinct from the former research. Additionally, we kicked out A from position 1, since its cleavage yield could not match that of the other three kinds of nucleotides.…”
Section: Discussioncontrasting
confidence: 63%
“…Despite the latest review of the HHRz, where the cleavage site sequence rule is still regarded as "NUX↓", 25 the study by Eckstein's group suggested that the rule could be revised to "NHH↓". 38 However, the study expected that the rate of GAC cleavage under single turnover conditions would be about 3%-7% compared to GUC, while our work reveals that the catalytic activity of GAC is almost equal to GUC, which is fairly distinct from the former research. Additionally, we kicked out A from position 1, since its cleavage yield could not match that of the other three kinds of nucleotides.…”
Section: Discussioncontrasting
confidence: 63%
“…Ribozyme-mediated inhibition of survivin expression M Pennati et al nucleotide but guanidine (Kore et al, 1998). These catalytic RNA motifs have received much attention in view of their potential usefulness for gene therapy due to their inherent simplicity, small size and ability to be incorporated into a variety of flanking sequence motifs without changing site-specific cleavage capacities.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, hammerhead ribozyme is very popular for the design of therapeutic ribozymes. On the other hand, the hairpin ribozyme has a more complex structure and requirements for target sequences, with a preference for GUC and cleavage occurring directly upstream of the G residue (Kore et al, 1998). An advantage of ribozyme over ASON is its catalytic mode of action, which should in principle require a much lower concentration of ribozymes as compared to non-catalytic ASONs.…”
Section: Ribozymesmentioning
confidence: 99%